Critical Impact of Storage Conditions on Kidney Biomarkers: Dampak Kritis Kondisi Penyimpanan pada Biomarker Ginjal - Intantri, Risma; Aliviameita, Andika; Puspitasari, Puspitasari; Rini, Chylen Setyo (Indonesian Journal on Health Science and Medicine, 2024)
This study investigated the impact of storage time (0, 4, 8, and 24 hours) at 2-8°C on urea and creatinine levels in serum samples from healthy young adults. Using a laboratory experimental design, 32 serum samples were analyzed with enzymatic and Jaffe-kinetic methods on a Microlab 300 photometer. Results from One Way ANOVA indicated significant effects on urea (p=0.007) and creatinine levels (p=0.009) across different storage times, with Post-Hoc tests revealing significant differences between the 0-hour and 24-hour storage groups for both biomarkers. These findings highlight the importance of standardized storage protocols in clinical laboratories to ensure accurate kidney function assessment and improve diagnostic reliability. Highlights: Storage Conditions Influence Biomarker Levels: Temperature and time affect urea and creatinine. Experimental Setup: Controlled lab study on serum samples with varying storage durations. Clinical Importance: Standard protocols ensure accurate kidney function assessment in diagnostics.. Keywords: kidney function, serum biomarkers, storage conditions, clinical laboratories, diagnostic reliability